(untitled) (Majalah Kedokteran Bandung, 2022)
Dengue is a disease caused by dengue virus (DENV) that is transmitted mainly by the female Aedes aegypti mosquito. There are four serotypes of DEN, leading to a possibility that a person may be infected four times by this virus, albeit with different serotypes. Recovery from infection with one viral serotype provides lifelong immunity to the same serotype but not to the other serotypes. Secondary infection by other serotypes increases the risk of developing severe dengue. The pathogenesis of severe dengue involves apoptosis of microvascular endothelial cells that leads to plasma leakage. In addition, there is usually a decrease in platelets and leukocytes and an increase in hematocrit. This study aimed to compare the results of the CD95L examination involved in the apoptotic process and the results of blood tests in primary and secondary dengue patients. This was a cross-sectional study performed in a four months period (September–December 2019) involving several clinics and doctor’s private practices in Medan, Indonesia. Subjects were eighty-four dengue patients, consisting of 18 (21%) patients with primary infection and 66 (79%) with secondary infection. Data collected were tested with the Mann Whitney test with p-value of <0.05 considered significant. A significant difference (p value=0.007) was observed in the lymphocyte counts between primary and secondary dengue patients, but no differences were seen in CDL95 level, platelet count, leukocyte count, and hematocrit. In conclusion, except for the lymphocyte count, there is no difference in CD95L level and blood test results between primary and secondary dengue patients.